Effects of long-term sprint interval training on work efficiency and acid-base balance in mountain bike cyclists - Hebisz, R.; Hebisz, P.; Zaton, M. (Medicina dello Sport, 2019)
BACKGROUND: The aim of the study was to evaluate the changes in work efficiency and acid-base balance after several months of systematic sprint interval training (SIT). METHODS: Thirty-one mountain bike cyclists with similar training experience were divided into an experimental and control group. Both groups executed an identical 8-month training macrocycle except training in experimental group was augmented to include a SIT component performed twice a week for the first 6 months. Each SIT session involved two to four sets of four 30 s all-out cycling bouts interspersed with 90 s of rest. The sets were separated by 25-40 min of moderate-intensity active recovery. Performance and biochemical changes were evaluated by a sprint interval testing protocol (SITP) consisting of three sets of four maximal sprints administered at baseline (SITP-0) and at 2 (SITP-2), 6 (SITP-6), and 8 (SITP-8) months. Outcomes including total work output, work efficiency, oxygen uptake, lactate and hydrogen ion concentrations were measured. RESULTS: Statistically significant changes were observed only in experimental group. Total work output and oxygen uptake increased at SITP-2, SITP-6, and SITP-8 compared with SITP-0. Hydrogen ion concentrations decreased at SITP-2 compared with SITP-0, and at SITP-6 compared with SITP-0 and SITP-2. A decrease in work efficiency was observed at SITP-6 compared with SITP-0 and at SITP-8 compared with SITP-2. CONCLUSIONS: The integration of a long-term SIT intervention can significantly enhance total work output in repeated maximal efforts alongside concomitant decrease in work efficiency, increase in aerobic energy cost and decrease acid-base disturbance.